Implementasi pelaksanaan program perlindungan anak di kota Semarang - Yuda Bagus Dwi PH; Suwanto Adhi (Journal of Politic and Government Studies, 2017)
Protection afforded to a child in an emergency situation. Sexual harassment can is defined as the act of sexual without agreement, motivation sexual behavior those involving children. Based on the discussion in the background problems basic want to proposed to be discussed in this research is: how do the implementation of the implementation of the program child protection in the city Semarang ( study on a body of women empowerment, child protection and family planning ( bp3akb ) through Bapermas PER and family planning the city of Semarang. ?All efforts made in the implementation of the implementation of the program child protection in the city Semarang ( study on a body of women empowerment, child protection and family planning ( bp3akb ) through bapermas per and family planning the city of Semarang.?Types of data on in this research there are two kinds of, namely types of data on primary and types of data on secondary. The study is done within the city of Semarang as for agencies which to base referral researchers are the empowerment of women, child protection and family planning BP3AKB. This research toward an object with research in violence children in the city of Semarang with reference in a body of women empowerment, child protection and family planning BP3AKB.through Bapermas per and family planning the city of SemarangImplementation of the child protection Program in the city of Semarang have not run optimally because the fulfillment of children's rights as mandated in Perda No. 5 2016 has not run optimally. Some of the rights of the child are still not being met as a right of identity, the right to basic needs, rights education and parenting rights. Child coaching programs which have been implemented already should be evaluated so that nothing can be known, the goal target, excess or shortcomings so that it can be used in the establishment of the next planning.Keyword::Children and women , child protection , women empowerment